TRADISI MATTAPUNG DALAM RITUAL KEMATIAN ETNIS BUGIS - Muh. Fajri Ramli (Bajang Institute, 2022)
The objective of this study is: (a) Explain the post-funeral ritual practice in Sinjai District, (b) Explain the elements of adat and religious elements that influence post-funeral rituals, and (c) Explain the implementation of the ritual mattampung based on Shari'a or adat.The method used in this study uses qualitative research methods. The data presented in the study are qualitative descriptive. This method was implemented with the objective of describing the Post-Funerary Ritual and explaining the ritual mattampung based on Shari'a or adat through theopinion of the community in the Sinjai District. Post-funeral rituals in the community are still important as a form of final respect for deceased family members. The community performs the ritual based on the knowledge they have. There are several processes that must be carried out in the rituals, from once the corpse is buried until the construction of its tomb. In post-funeral rituals there are also religious or customary elements that can be seen in their implementation. The community considers mattampung, which is one of the stages of the postfuneral ritual, to be carried out on the basis of adat.